2017
DOI: 10.1021/jacs.7b11491
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Surface of Gold Nanoclusters by Cadmium Doping

Abstract: Atomically precise metal nanoclusters with tailored surface structures are important for both fundamental studies and practical applications. The development of new methods for tailoring the surface structure in a controllable manner has long been sought. In this work, we report surface reconstruction induced by cadmium doping into the [Au(SR)] (R = cyclohexyl) nanocluster, in which two neighboring surface Au atomic sites "coalesce" into one Cd atomic site and, accordingly, a new bimetal nanocluster, [AuCd(SR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 44 publications
3
115
0
Order By: Relevance
“…Li et al reported that Cd doping can induce reconstruction of the surface of gold nanoclusters. [234] For example, the structure of [Au 19 Cd 2 (SR) 16 ] − (SR = S-c-C 6 H 11 ) shows one pair of Cd[Au(SR) 2 ] 3 staple motifs on the two opposite sides of the kernel (Figure 15a). In each Cd[Au(SR) 2 ] 3 motif, three monomeric Au(SR) 2 are merged at the Cd atom to form a "paw-like" configuration in quasi-C 3 symmetry (Figure 15a, inset (Figure 15b), [235] only one Cd[Au(SR) 2 ] 3 is identified on the surface, and one CdSH unit as well; thus, the single motifs contribute to the chirality of the bimetal Au 20 Cd 4 cluster.…”
Section: Cd-thiolate Surface Structuresmentioning
confidence: 99%
“…Li et al reported that Cd doping can induce reconstruction of the surface of gold nanoclusters. [234] For example, the structure of [Au 19 Cd 2 (SR) 16 ] − (SR = S-c-C 6 H 11 ) shows one pair of Cd[Au(SR) 2 ] 3 staple motifs on the two opposite sides of the kernel (Figure 15a). In each Cd[Au(SR) 2 ] 3 motif, three monomeric Au(SR) 2 are merged at the Cd atom to form a "paw-like" configuration in quasi-C 3 symmetry (Figure 15a, inset (Figure 15b), [235] only one Cd[Au(SR) 2 ] 3 is identified on the surface, and one CdSH unit as well; thus, the single motifs contribute to the chirality of the bimetal Au 20 Cd 4 cluster.…”
Section: Cd-thiolate Surface Structuresmentioning
confidence: 99%
“…Single‐crystal X‐ray diffraction revealed that the recrystallization crystal has the same metal core structure with Eu 52 Ni 56 , suggesting the integrity of Eu 52 Ni 56 after hydrothermal reaction. Energy dispersive X‐ray spectroscopy (EDX) elemental mapping of the crystal indicates that some of the Ni 2+ was replaced by Cd 2+ during the hydrothermal reaction and then formed the metal exchanged heterometallic 4f–3d–4d cluster [Ln 52 Ni 56− x Cd x (IDA) 48 (OH) 154 (H 2 O) 38 ] 18+ (labeled as Ln 52 Ni 56− x Cd x ) (Figure S5, S6) . The inductively coupled plasma spectrometry (ICP‐MS) results demonstrate that the substitution percentage is approximately 20 % (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…This readily means that Cd(SR) 2 may prompt a similar oxidation‐induced size conversion reaction of [Au 23 (SR) 16 ] − (toward [Au 28 (SR) 20 ] 0 ), which takes place concurrently with a substitution reaction of 2 Au → 1 Cd. Isoelectronic size conversion from [Au 23 (SR) 16 ] − to [Au 19 Cd 2 (SR) 16 ] − could also be accomplished via similar substitution of four surface Au atoms of the former by two Cd heteroatoms …”
Section: Synthesis Of Metal Ncs Via Cluster‐conversion Strategymentioning
confidence: 99%